Biomass and biofuels in China: Toward bioenergy resource potentials and their impacts on the environment. (February 2018) - Qin, Zhangcai; Zhuang, Qianlai; Cai, Ximing; He, Yujie; Huang, Yao; Jiang, Dong; Lin, Erda; Liu, Yaling; Tang, Ya; Wang, Michael Q.
Abstract: Bioenergy can be a promising solution to the energy, food and environment trilemma in China. Currently this coal-dependent nation is in urgent need of alternative fuels to secure its future energy and improve the environment. Biofuels derived from crop residues and bioenergy crops emerge as a great addition to renewable energy in China without compromising food production. This paper reviews bioenergy resources from existing conventional crop (e.g., corn, wheat and rice) residues and energy crops (e.g., Miscanthus ) produced on marginal lands. The impacts of biofuel production on ecosystem services are also discussed in the context of biofuel's life cycle. It is estimated that about 280 million metric tons (Mt) of crop residue-based biomass (or 65 Mt of ethanol) and over 150 Mt of energy crop-based ethanol can become available each year, which far exceeds current national fuel ethanol production (< 2 Mt year −1 ) and the 2020 national target of 10 Mt year −1 . Review on environmental impacts suggested that substituting fossil fuels with biofuels could significantly reduce greenhouse gas emissions and air pollution (e.g., particulate matter). However, the impacts of biofuel production on biodiversity, water quantity and quality vary greatly among biomass types, land sources and management practices. Improved agricultural management and landscape planning can be beneficial to ecosystem services. A national investigation is desirable in China to inventory technical and economic potential of biomass feedstocks and evaluate the impacts of biofuel production on ecosystem services and the environment.